Strengths and weaknesses of social studies instruction at Balara Elementary School - Balonso, Celinia E. (1979)
This study aimed to determine how the social studies subject is viewed, handled, and imparted to the children in one of the public schools in Quezon City, considering the vital factors affecting the teaching-learning situation. The major tool used in this study was a questionnaire which was issued to thirty social studies elementary teachers of Balara Elementary School in Quezon City. It was found that the "New" social studies can be implemented since school facilities, teaching materials, and teacher competency are adequate although the administrators' assistance do not suffice. The respondents also do not have yet a full grasp of what the "new" social studies is. Several solutions were given by the respondents to improve the present status of social studies instruction in Balara Elementary School.